An engineering approach for the estimation of slewing bearing stiffness in wind turbine generators. Issue 3 (30th November 2018) - Heras, Iker; Aguirrebeitia, Josu; Abasolo, Mikel; Coria, Ibai
Abstract: The stiffness of yaw and pitch slewing bearings has a critical influence on the structural behaviour of wind turbine generators. Thus, it is commonly required by designers for their simulations to estimate deformations and select the most suitable bearing for their working conditions in preliminary design stages. In this work, a design of experiments was carried out via finite element analysis to obtain the stiffness curves of all of the standard four‐point contact slewing bearings from the catalogues of manufacturers under radial, axial, and tilting loads. From these results, a set of simple formulas to calculate the ring deformations were adjusted. Combining them with contact deformation results obtained in previous work by the authors, a complete and efficient tool for slewing bearing stiffness estimation has been developed.